The Effect Of Spiritual Moral Development On Student Victims Of Divorce Through Humanist Counseling Guidance Approach At SMK PGRI 2 Kediri - Mumajad, Ma’ma; Alfiah Nurcholidah; Firnanda Erindia (Jurnal Pendidikan dan Konseling (JPDK), 2022)
Divorce is a condition where parents are not in harmony, often fight and cause commotion, which results in a lack of love and care for children, so that children will no longer have someone to protect or serve as role models for them. This research will focus on on the process and results of the spiritual moral development of students who are victims of parental divorce through a humanist counseling approach. This type of research uses descriptive qualitative methods, the data sources in this study use observations, interviews, and documentation studies. While the key instrument is the research itself. The data were analyzed by reducing the data, presenting the data, and drawing conclusions. This study contains the results (1) Behavioral patterns of students who are victims of Broken Home at SMK 2 PGRI Kediri, these students tend to have unfavorable traits such as: truancy, smoking, being late. (2) The Process of Spiritual Moral Development for Broken Home Students Through a Humanist Counseling Guidance Approach at SMK 2 PGRI Kediri by participating in religious activities such as: dhuha prayer, istigosah (3) The results of broken home students after spiritual moral coaching through a humanist counseling guidance approach, students become more good and aware. Keywords: Spiritual Moral Development, Student, Divorce, Humanist Counseling